Multi‐organ dysfunction due to bath salts: are we aware of this entity?. Issue 1 (January 2017) - Valsalan, Rohith; Varghese, Benoj; Soman, Diya; Buckmaster, Jonathan; Yew, Steven; Cooper, David
Abstract : Methylenedioxypyrovalerone (MDPV) is a synthetic, cathinone‐derivative, central nervous system stimulant taken to produce a cocaine‐ or methamphetamine‐like high. Physical manifestations include tachycardia, hypertension, arrhythmias, hyperthermia, sweating, rhabdomyolysis, hyperkalaemia, disseminated intravascular coagulation, oliguria and seizures. We report a patient who presented with severe metabolic acidosis, multi‐organ dysfunction, rhabdomyolysis, hyperkalaemia and seizures. This case highlights that even though a urine drug screen for routine psychostimulant drugs is negative, clinicians need to be vigilant about the adverse effects of MDPV as a possible cause of multi‐organ dysfunction. Substances such as this can only be detected by special tests, such as gas/liquid chromatography mass spectrometry. This is the first reported case of MDPV toxicity successfully treated in Australia to the best of our knowledge.